Analysis of instantaneous frequency, instantaneous amplitude and phase angle of ferroresonance in electrical power networks - (:unkn) unknown (SLOVAK UNIV TECHNOLOGY, 2019)
Ferroresonance is a nonlinear phenomenon that damages the undesired, destructive system for energy transmission lines. The formation and development of this overvoltage ferroresonance phenomenon is an important research topic as a mysterious event in energy power systems. In this study, Seyit Omer-Iklar energy transmission line from Turkey's electrical transmission networks was modelled using real parameters. Ferroresonance scenario was created on the model. The energy transmission system with the scenario is set to a simulation time of 4 seconds. The first two seconds are set to normal. By cutting off the transmission line in the 2nd sec., the system is provided with ferroresonance drift. According to the data obtained therefrom, spectrograms, instantaneous amplitude, instantaneous frequency and instantaneous phase were conducted. The analyses have made clear that the instantaneous frequency amplitude defined the system's ferroresonance moment very well.
Keywords: Hilbert-Huang transform; ferroresonance; spectrograms; instantaneous frequency; instantaneous phase